Image-guided techniques for localization of pulmonary nodules during video-assisted thoracoscopic surgery lobectomy - Coco, Danilo; Leanza, Silvana; Bastone, Sebastiano Angelo; Viola, Massimo Giuseppe; Ambrogi, Vincenzo (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2023)
In the modern era when screening and early surveillance of pulmonary nodules are increasing in importance, the management of the pulmonary nodule represents a different challenge to thoracic surgeons. The difficulty lies in the merging of sound surgical and oncological principles with more minimally invasive and appropriate lung-sparing surgery. The success rates of video-assisted thoracoscopic surgery (VATS) resection for smaller as well as subsolid nodules have increased as a result of radiologists’ preoperative localization tools. Fast tracking in thoracic surgery is promoted by proper postoperative care for patients having lobectomies in combination with the VATS technique. Image-guided surgery refers to the application of a real-time correlation of the surgical field to preoperative imaging data collection that reflects the precise placement of a chosen surgical instrument in the adjacent anatomic structures. Among the cross-sectional digital imaging techniques the most widely utilized imaging modalities for image-guided therapy are computed tomography and magnetic resonance imaging. Additionally, surgical navigation devices, tracking tools, integration software, ultrasound, and angiography are used to support these procedures. For people who are thinking about implementing or optimizing a nodule localization program in view of workflow patterns, surgeon preferences, and institutional resources in a certain facility, this review provides in-depth, unbiased evaluation and offers useful information.